Participatory Training: A Solution to Dealing with Livelihood Loss due to Environmental Change - Maulana, Hasan Tafsir; Sudiapermana, Elih; Sulistiono, Eko; Shantini, Yanti (ITScience (Information Technology and Science), 2024)
This study aims to analyze the participatory training organized by PKBM Maharani Sumedang and its impact on livelihood change and community empowerment. The training was specifically designed to restore the self-reliance of affected community members by equipping them with the skills to make shredded fish, which utilizes local natural resources. Using a qualitative approach with descriptive methods, this study aimed to gain an in-depth understanding of the training process and outcomes. Data collection techniques included interviews, observations, questionnaires and documentation to obtain comprehensive views from participants, trainers and community leaders. Triangulation was applied to ensure data reliability, while data were analyzed through reduction, display, and conclusion drawing or verification. The results showed that the training used a participatory approach in accordance with the needs, skill levels and resource potential of the local community. This approach not only actively involved participants but also tailored the training to realistic economic opportunities in the area. The training fosters self-reliance, allowing community members to use their newly acquired skills to create alternative livelihoods. By utilizing available fish resources, residents can now generate a sustainable income that complements the natural environment in the region. This initiative highlights a successful model for community-based training programs, demonstrating how participatory training can drive livelihood change and long-term resilience for communities affected by large-scale infrastructure projects.